2000
DOI: 10.1029/2000ja900006
|View full text |Cite
|
Sign up to set email alerts
|

On the location of trapped particle populations in quadrupole magnetospheres

Abstract: Abstract. Populations of trapped particles in Earth's magnetic field are intimately linked to prominent magnetospheric phenomena, for example, to the radiation belts and the ring current. Particles are forced to bounce between both hemispheres because field lines converge from the magnetic equatorial region toward the poles owing to the dominating dip olaf component. The scenario may change essentially if the so-called paleomagnetosphere is considered, that is, the terrestrial magnetosphere during a polarity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Also, the effect of energetic particles in the magnetosphere is not discussed here. A first discussion on this can be found in the work by Vogt and Glassmeier (2000).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effect of energetic particles in the magnetosphere is not discussed here. A first discussion on this can be found in the work by Vogt and Glassmeier (2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the total dipole magnetic field energy is transferred to quadrupole or octupole moments (Vogt & Glassmeier 2000;Zieger et al 2004). Therefore, the quadrupole component can be strong enough to generate a fully pledged magnetosphere, as well as to prevent the solar wind from directly impacting the atmosphere (at least in some parts of the globe).…”
Section: Quadrupolar Mini-magnetospherementioning
confidence: 99%
“…To get a simple approximation for the magnetic field line topology in the magnetosphere, the inner dipole field and the ring current field are combined to a magnetic field of a modified dipole moment. Vogt and Glassmeier (2000) showed that in quadrupole magnetospheres the configuration and location of the ring current may be totally different from the present situation. In some cases one cannot even speak of a ring current any more.…”
Section: Internal Field and External Current Systemsmentioning
confidence: 99%
“…Galactic cosmic rays may have an influence on cloud coverage, which in turn influences the global radiation budget and thus the climate (Svensmark and Friis-Christensen, 1997;Marsh and Svensmark, 2000). Trapped particle populations and ring current geometries in quadrupolar magnetospheres were studied by Vogt and Glassmeier (2000). The scaling behavior of different classes of energetic particles in dipolar and quadrupolar paleomagnetospheres was investigated by Vogt et al (2007).…”
Section: Introductionmentioning
confidence: 99%